The role of English education in environmental awareness: A secondary data review within Indonesian and comparative global contexts - Muhammad Wildan Al Faqih (Asian Journal Collaboration of Social Environmental and Education, 2026)
Background: Environmental degradation in Indonesia home to globally significant ecosystems yet facing persistent challenges of deforestation, pollution, and climate-related disasters demands systemic educational responses that extend beyond science-based curricula. Despite the potential of English language teaching (ELT) to serve as a vehicle for environmental awareness, this role remains underexplored and underutilized in Indonesian educational contexts. Methods: This study conducted a secondary data review of 63 open-access journal articles, curriculum documents, government reports, and academic publications from 2021 to 2024, sourced from databases including DOAJ, Google Scholar, ERIC, ResearchGate, and SINTA-accredited Indonesian journals. Inclusion criteria required publications to demonstrate explicit relevance to ELT, environmental awareness, Indonesian educational settings, and peer-reviewed academic quality; exclusion criteria eliminated pre-2021 publications, restricted-access materials, and non-educational sources. Data were analyzed through thematic content analysis following a four-stage process of familiarization, coding, theme development, and interpretive synthesis. Findings: The review identified four primary mechanisms through which English education supports environmental awareness: curriculum integration of environmental themes, exposure to authentic ecological resources, development of communicative and critical eco-literacy skills, and formation of global environmental identity. Findings further revealed that national-level policy gaps, limited teacher preparedness in eco-pedagogy, resource inequalities, and exam-driven instructional cultures constrain consistent implementation. Conclusion: Comparative evidence from Finland, Japan, and Malaysia demonstrates that countries with national mandates for sustainability-oriented ELT achieve measurably stronger environmental literacy outcomes. Novelty/Originality of this article: This study contributes to the growing body of eco-linguistic scholarship by providing the first systematic synthesis of Indonesian ELT literature specifically examining environmental awareness between 2021 and 2024, offering an evidence base for curriculum reform, teacher education, and policy development aligned with Education for Sustainable Development (ESD) goals.